Pay-as-you-speed: An economic field-experiment - Lars Hultkrantz; Gunnar Lindberg (Örebro University School of Business, 2009)
We report a vehicle-fleet experiment with an economic incentive given to car drivers for keeping within speed limits. A pay-as-you-speed traffic insurance scheme was simulated with a monthly participation bonus that was reduced by a non-linear speeding penalty. Actual speed was monitored by a GPS in-vehicle device. Participating drivers were randomly assigned into two-by two treatment groups, with different participation-bonus and penalty levels, and two control groups (high and low participation bonus, but no penalty). A third control group consists of drivers with the same technical equipment who did not participate but whose driving could be monitored. We evaluate changes in behaviour from twelve-month differences in proportion of driving time per month that the car was exceeding the maximum allowed speed on the road. We find that the participating drivers significantly reduced severe speeding violations during the first experiment month, while in the second experiment month, after having received feedback reports with an account of earned payments, only those participating subjects that were given a speeding penalty reduced severe speed violations. We find no significant effects from the size of the participation bonus (high vs. low), or the size of the penalty (high vs. low rate).
Keywords: H23; I18; K42; R41; 330; Traffic insurance; traffic safety; Intelligent Transport Systems; ITS; Intelligent Speed Adaptation; ISA